2016
DOI: 10.1186/s13014-016-0691-x
|View full text |Cite
|
Sign up to set email alerts
|

High-risk factors of parotid lymph node metastasis in nasopharyngeal carcinoma: a case-control study

Abstract: BackgroundAlthough parotid-sparing IMRT decreased the dose distribution of parotid, parotid region recurrence has been reported. Prophylactic irradiation in parotid area would be necessary in patients with high risk of parotid lymph node metastasis (PLNM). This study was to detect the high-risk factors of PLNM in nasopharyngeal carcinoma.MethodsThis was a 1:2 case-control study. All patients in this study were newly diagnosed NPC with N2-3 classification from January 2005 to December 2012. Cases were 22 sides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Our results showed that the incidence of PLN metastasis was only 2.8%, which was similar to rates in other studies .Due to the low frequency of initial PLN metastasis with NPC, little attention has been paid to this condition in clinical practice. To the best of our knowledge, PLN metastasis has not yet been classified in the 7th UICC/AJCC staging system or the Chinese 2008 staging system for NPC.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results showed that the incidence of PLN metastasis was only 2.8%, which was similar to rates in other studies .Due to the low frequency of initial PLN metastasis with NPC, little attention has been paid to this condition in clinical practice. To the best of our knowledge, PLN metastasis has not yet been classified in the 7th UICC/AJCC staging system or the Chinese 2008 staging system for NPC.…”
Section: Discussionsupporting
confidence: 88%
“…Nasopharyngeal carcinoma (NPC) is the most commonly diagnosed head and neck malignancy in Southeast Asia, with unique aggregation in Southern China. Although 85% of cases of preliminarily diagnosed NPC involve cervical lymph node metastasis , parotid area lymph node (PLN) metastasis is rare, with an incidence rate of only 1–3.4% . In addition, the PLN is generally regarded as an unconventional surgical neck dissection area .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, NPC has a high incidence of lymph node metastasis and occurs in a majority of the patients prior to their first visit to the clinic (97,98). The demand to improve the efficacy of anti-NPC therapy has prompted the identification of genes that are implicated in lymph node involvement, which is an indicative of disease progression and therapeutic failure (99)(100)(101). Thus, the investigation of the role of miRs in NPC may provide a mechanistic explanation of lymph node metastasis, as well as more a sensitive indicator for the prognosis of NPC.…”
Section: Ebv-encoded Mirs As Biomarkers For the Diagnosis And Prognosmentioning
confidence: 99%
“…It has extremely skewed ethnic and geographic distributions, which is a rare malignant tumor in Western countries, but is one of the most prevalent cancers in the southern region of the People’s Republic of China and Southeast Asia 35. At present, radiotherapy and radiochemotherapy are the major means of treating NPC, but because of its high metastasis, a significant proportion of patients still develop neck and distant metastasis and the prognosis of these patients remains poor 6,7. Therefore, further explorations of the molecular mechanisms of NPC carcinogenesis and more effective therapeutic strategies are urgently required.…”
Section: Introductionmentioning
confidence: 99%